1991
DOI: 10.1128/aac.35.1.208
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of Clostridium difficile intestinal colonization and disease following single-dose antibiotic prophylaxis in surgery

Abstract: A total of 108 volunteers undergoing an elective surgical procedure were randomly given a single 2-g intravenous prophylactic dose of either a cephalosporin or mezlocillin. Stool samples were cultured for Clostridium difficile the day before the operation and later on postoperative days 4, 7, and 14. C. difficile was detected in 23.0% of patients who received a cephalosporin (cefoxitin, 8.3%; cefazolin, 14.3%; cefotetan, 20.0%; ceftriaxone, 25.0%; cefoperazone, 43.7%), in 3.3% of patients given mezlocillin, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(58 citation statements)
references
References 31 publications
2
52
1
3
Order By: Relevance
“…The isolation rate of 6.3% in our patients treated with ceftriaxone for 14 days was significantly lower (P < 0.0005) than that from a study by Privitera et al (12), who found C difficile in stools of 25% patients receiving ceftriaxone as a single dose for perioperative prophylaxis. The rate of isolation was also lower than expected according to our own experience.…”
contrasting
confidence: 46%
“…The isolation rate of 6.3% in our patients treated with ceftriaxone for 14 days was significantly lower (P < 0.0005) than that from a study by Privitera et al (12), who found C difficile in stools of 25% patients receiving ceftriaxone as a single dose for perioperative prophylaxis. The rate of isolation was also lower than expected according to our own experience.…”
contrasting
confidence: 46%
“…Although the selection of C. difficile in fecal flora 9 and the anecdotal occurrence of CDAD following even a single dose of antibiotics are well reported, 10,11,12 prophylactic antibiotics have not been shown to be a specific risk factor for developing CDAD. 13 The large proportion of patients in both groups receiving exclusively prophylactic antibiotics (44% and 45%) reflects the frequency of surgical intervention in our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Any factor that alters the colonic flora increases the risk of C. difficile infection. Antibiotic treatment, especially broad spectrum, is the predominant risk factor for colonization that leads to C. difficile proliferation and disease (5,38). The physiological and metabolic changes in C. difficile that underlie infection during or after antibiotic stress are not known.…”
Section: Resultsmentioning
confidence: 99%